The Implementation of The Merdeka Curriculum in English Subject at A Vocational High School in Indonesia - Ferdaus, Shinta Amalia; Novita, Dian (BRILIANT: Jurnal Riset dan Konseptual, 2023)
This study aims to analyze the implementation of the Merdeka Curriculum in English subject at one of the vocational high schools in Sidoarjo as the Centre of Excellence of Vocational High School (SMK PK). The study used the descriptive-qualitative method as the research design, and the data were obtained through observations and semi-structured interviews. The subject of this study was an English teacher for 11th graders, and the data sampling used was purposive random sampling in the 11th-grade class. The present study focused on the following six areas regarding the implementation of the Merdeka Curriculum: 1) the implementation of the teaching module, 2) the teaching and learning process, 3) the use of learning materials, 4) the use of learning media, 5) the implementation of assessment and evaluation, and 6) the opportunities and obstacles. The study results found that the Merdeka Curriculum at one of the vocational high schools has been widely implemented. However, obstacles arise related to perceptions changing from teacher-centered learning to student-centered learning. All approaches taken in the teaching and learning process of English learning have resulted in a student-centered approach, which is also consistent with the Pancasila Student Profile outcomes. The integration of Pancasila Student Profile orientation and student-centered approach in English learning is intended to produce generations that are self-sufficient, capable of critical, creative, and innovative thinking, quickly sociable, and capable of communicating and collaborating. In addition, the principle of freedom that is upheld in this Merdeka curriculum has been able to encourage students and teachers to maximize teaching and learning processes that are more meaningful.